(untitled) (BRAC University Journal, 2026)
This comparative study was carried out to investigate the presence of antibiotic sensitive and resistant bacteria isolated from different environmental samples of Bangladesh with specific clinical strain obtained from !CD DR, B . The environmental isolates were collected from the month April 2015 to September 2015 from different locations ofDbaka city to perceive the propensity of these environmental isolates to develop antibiotic resistance at different time periods of a year. The bacterial isolates were identified on the basis of the standard cultural, morphological and biochemical characteristics. Antibiogram was done to identiJY the antibiotic susceptibility of the isolates according to CLSI guidelines. The result of this study showed that all the environmental isolates have become resistant to the tested antibiotics, and some of them have become multiresistant to these therapeutic agents whereas all the clinical isolates showed the opposite result. The study helps to predict the future emergence and to guide the development of strategies towards counteracting this resistance. Therefore periodic and comprehensive survey of antibiotic resistance in the environmental bacteria is required